ENaC inhibitors for the treatment of cystic fibrosis. (January 2015) - Butler, Rebecca; Hunt, Thomas; Smith, Nichola J
The epithelial Na + channel, ENaC, is a key regulator of the volume of airway surface liquid in the human airway epithelium. In cystic fibrosis (CF), Na + hyperabsorption through ENaC in the absence of CFTR-mediated anion secretion results in the dehydration of respiratory secretions and the impairment of mucociliary clearance. The hypothesis of utilizing an ENaC-blocking molecule to facilitate restoration of the airway surface liquid volume sufficiently to allow normal mucociliary clearance is of interest in the management of lung disease in CF patients. This article summarizes the published patent applications from 2010 that claim approaches to inhibit the function of ENaC for utility in the treatment of CF. Patents were located though SciFinder ®, using "ENaC" as the keyword from 2010 onwards; documents not relevant to CF were then manually removed.